Associations of Abnormal Sleep Duration with Occupational and Leisure-time Physical Activity in the Working Population: A Nation-wide Population-based Study - Myeonghun Beak; Won-Jun Choi; Wanhyung Lee; Seunghon Ham (Elsevier, 2021)
Background: The present study investigated the association between two domains of physical activity (occupational physical activity [OPA] and leisure-time physical activity [LTPA]) and sleep duration. Methods: We investigated 3,421 paid workers from the Korea National Health and Nutrition Examination Survey, 2014-2015. Sleep duration was categorized into three categories (short for less than 5 h, optimal for 5-9 h, and long for more than 9 h). OPA and LTPA were defined in terms of answers to relevant questions. Odds ratios were calculated for sleep duration according to each physical activity domain using multinomial logistic regression models. Results: There were 464 subjects (13.6%) who showed short sleep duration, and 169 subjects (4.9%) who showed long sleep duration. Prevalence of OPA and LTPA was higher in male workers than in female workers (for OPA: 3.67% and 1.76%, respectively, p = 0.0108; for LTPA: 16.14% and 6.07%, respectively, p < 0.0001). The odds ratio of OPA for long sleep duration in female workers was 3.35 (95% confidence interval, 1.37-8.21). Otherwise, LTPA was not associated with sleep duration in female paid workers, nor both physical activity domains in male paid workers. Conclusion: Female paid workers with work-related physical activity were at risk of oversleeping. These findings also suggested that physical activity has distinct associations with sleep duration according to the physical activity domains and sex.